MODEL ACCELERATED LEARNING PENDIDIKAN AGAMA ISLAM - Anam, Haerul (Jurnal El-Hamra : Kependidikan dan Kemasyarakatan, 2017)
Accelerated learning is one of the results of innovation in education. Programming is done because the demands of the times is developing very fast. Bulgarian psychiatrist Georgi Lozanov Accelerated Learning is the originator of the movement. The learning model Accelerated Learning is a pattern used in learning that is designed such that it can arouse the learning ability of students, making learning more fun and faster. Accelerated learning is the philosophy of learning and life seeking re demekanisasi and humanize the learning process, as well as making the experience for the whole body, the whole mind, and the whole person. Accelerated Learning, it will not benefit them separating its methods of ideological foundation, and ignores the principles which underlie these techniques. Dave Meier, suggested to teachers in order to manage classroom approach Somatic, Auditory, Visual and Intellectual (SAVI). Somatic intended as learning by doing (learning by moving and doing). Auditory is learning by talking and hearing (learned by talking and listening). Visual means learning by observing and picturing (learning by observing and describing). Intellectual intention is learning by problem solving and reflecting (learning with problem solving and reflection). Technically, there are stages that must be passed in operating the learning model Accelerated Learning (accelerated learning). Among them are: 1. Mechanical Preparation, preparation phase with regard to preparing learners for learning; 2. Submission Techniques, the delivery stage learning cycle intended to bring together learners with learning materials that initiate the learning process in a positive and attractive; 3. Technical Training, the training stage (integration) is the essence of Accelerated Learning (accelerated learning); 4. Appearance techniques, helping students apply and develop their knowledge and new skills on the job so that learning achievement remain attached and continue to rise. Key Words: Accelerated Learning, Learning Model, Somatic, Auditory, Visual and Intellectual (SAVI)